Evaluation Of Lipid Profiles, Dyslipidemia and Atherogenic Index of Plasma in Diabetic Patients - Madhikarmi, Nirjala Laxmi; Tamrakar , Supriya Shrestha (Journal of Manmohan Memorial Institute of Health Sciences, 2024)
Objective: To study the pattern of lipid profile, dyslipidemia and atherogenic index of plasma in Diabetic patients. Method: A case-control study was conducted among 1024 individuals; 512 diabetics and 512 were healthy controls at Kantipur General Hospital, Basundhara in between January 2019 to December, 2021. Lipid profile tests; total Cholesterol, triglyceride, high density lipoprotein (HDLC), low density lipoprotein (LDL) was measured on automated analyzer and ratios were calculated. Findings: 61.2% of patients showed dyslipidemia, 34% hypertriglyceridemia, 73.4% had low HDL (<40mg/dl) and 93.8% atherogenic index of plasma (AIP) >0.21. Hypo-HDL-cholesterolemia was prevalent dyslipidemia in our study. Pearson correlation coefficient of total cholesterol, triglyceride, HDL, LDL, total lipids, AIP were 0.688, 0.917, 0.069, 0.182, 0.17, 0.901, 0.744 respectively on glucose-gender basis. Conclusion: Dyslipidemia is one of the major risk factors which is widely prevalent in patients with diabetic mellitus and is more prevalent in males. We recommend paying more attention to serum lipids, modifiable risk factors like proper diet, medication, eating habits and physical exercises for its prevention.